How it feels to be American - Devitt, Allison G. (Young Scholars Grinchenko – Seton International Journal, 2025)
I was born free. Nevertheless, I never earned it. My life has been marked by the comfort of living on a quiet street in the suburbs of America, with a loving family, warm dinners, and yearly summer vacations to carefree destinations. A middle-class white 19-year-old girl from New Jersey is now studying as an elementary education major, following in her parents' footsteps. To many, my life is ordinary and predictable. However, in my eyes, I see 250 years of resistance, sacrifice, and progress that those generations before me had built upon. When I hear "America," I hear country music on the radio, ketchup-covered hot dogs at summer barbecues, and fireworks booming in the sky on the Fourth of July. I see red, white, and blue flags hung proudly on my front porch and folding chairs lined up on the lawn to watch the Memorial Day parade pass. Being American means attending the high school football games on Friday nights and cheering as loudly as possible when you hear "The land of the free, and the home of the brave."